Novel suspension retroviral packaging cells generated by transposition using transposase encoding mRNA advance vector yields and enable production in bioreactors - van Heuvel, Yasemin; Schatz, Stefanie; Hein, Marc; Dogra, Tanya; Kazenmaier, Daniel; Tschorn, Natalie; Genzel, Yvonne; Stitz, Jörn (Frontiers in Bioengineering and Biotechnology, 2023)
To date, the establishment of high-titer stable viral packaging cells (VPCs) at large scale for gene therapeutic applications is very time- and cost-intensive. Here we report the establishment of three human suspension 293-F-derived ecotropic MLV-based VPCs. The classically used stable transfection of a EGFP-expressing transfer vector resulted in a polyclonal VPC pool that facilitated cultivation in shake flasks of 100 mL volumes and yielded high functional titers of more than 1 x 106 transducing units/mL (TU/mL). When the transfer vector was flanked by transposon terminal inverted repeats (TIRs) and upon co-transfection of a plasmid encoding for the transposase, productivities could be slightly elevated to more than 3 x 106 TU/mL. In contrast and using mRNA encoding for the transposase as a proof of concept, productivities were drastically improved by more than ten-fold exceeding 5 x 107 TU/mL. In addition, these VPC pools were generated within only three weeks. The production volume was successfully scaled up to 500 mL employing a stirred-tank bioreactor (STR). We anticipate that the stable transposition of transfer vectors employing transposase transcripts will be of utility in the future establishment of high-yield VPCs producing pseudotype vector particles with a broader host tropism in large scale.